Validity and Reliability Testing of the Modified Indonesian Version of the Smartphone Addiction Scale-Short Version - Priscilla Rosita Putri Nurmasari; Lilik Ariyanti; Almas Awanis (Global Health Science Group, 2026)
Smartphone usage has increased rapidly worldwide, making the potential for smartphone addiction a focus of research. To identify potential smartphone addicts, several scales have been developed to assess smartphone addiction; among them, the Smartphone Addiction Scale-Short Version (SAS-SV) is frequently used. This study aimed examine the reliability and validity of the Indonesian version of the SAS-SV. A cross-sectional research design with a population consisting of 100 of Pharmacy students at Farmasi Nasional Vocational High School in Surakarta. Data were analyzed using SPSS; validity was established by showing that the calculated r-value exceeded the r-table value, while reliability was assessed using Cronbach's alpha. The evaluation showed that the research instrument possesses robust validity and reliability. Internal consistency analysis yielded a Cronbach's alpha coefficient of 0.980, substantially exceeding the acceptable threshold of 0.60. Furthermore, construct validity was confirmed as the calculated r-values for all ten items ranged from 0.853 to 0.939, consistently surpassing the critical r-table value of 0.195 (n = 100).